(untitled) (International Journal of Environmental Sciences, 2025)
Background: Nintedanib, a multi-target tyrosine kinase inhibitor, slows progression of fibrotic interstitial lung diseases (ILDs) but is frequently complicated by adverse drug reactions (ADRs). This prospective observational study evaluated the incidence, predictors, and management of Nintedanib-associated ADRs in an Indian tertiary-care cohort. Methods: Thirty patients with fibrotic ILD received Nintedanib 150 mg twice daily and were followed over six months. Demographic, clinical data were collected. ADRs were coded by type and severity; causality was assessed using the WHO-UMC scale. Associations between patient characteristics and key ADRs (notably diarrhea) were examined via chi-square tests and independent t-tests. Logistic regression identified independent predictors of dose modification. Spearman’s correlation assessed the relationship between total ADR burden and treatment duration. Results: A total of 143 ADRs (mean 4.8 per patient) were recorded. Fatigue (70.0%) and diarrhea (60.0%) were most common; liver-function abnormalities occurred in 56.7%. Female sex (66.7% vs. 11.1%, p = 0.006) and advanced age (68.5 vs. 60.5 years, p = 0.017) were significantly associated with diarrhea development. Diarrhea emerged as the strongest predictor of dose modification (β = 2.50, p < 0.001). Sixty percent of patients required dose reduction or temporary interruption; Spearman’s ρ = –0.335 (p = 0.071) indicated a trend toward shorter treatment duration with higher ADR burden. WHO-UMC causality assessment classified 55.5% of diarrhea cases as “Certain” or “Probable.” Conclusion: In this real-world Indian cohort, Nintedanib therapy incurred a high ADR burden, particularly gastrointestinal toxicity in older and female patients, leading to frequent dose adjustments. Most ADRs were manageable through supportive care and patient education, enabling continued treatment. These findings underscore the need for proactive monitoring and individualized management strategies, and they provide novel region-specific pharmacovigilance data to inform global ILD care.